A retrospective radiographic analysis of osseous changes in oral malignancy - Palak H Shah; Rashmi Venkatesh; Chandramani B More; Vaishnavee Vassandacoumara (Wolters Kluwer Medknow Publications, 2016)
Introduction: Although oral squamous cell carcinoma mainly occurs in oral soft tissues, involvement of jaw bones occurs in 12-56% of the cases. In these cases, radiographic examination becomes important to observe the pattern of bone involvement. Objectives: To analyze the radiographic features of oral malignancy involving jaw bone and to compare it with the available literature. Materials and Methods: The clinical and radiographic records of 20 cases of oral malignancy showing bone involvement in panoramic radiographs were analyzed from the archives of the department in the present hospital-based retrospective study. Descriptive statistics were used to compare the findings. Results: We observed that the age of the patients presenting with oral malignancy with jaw bone involvement ranged from 35 to 82 years, with a male:female ratio of 1:1. Mandible was involved in 19 cases with preference to the right side (63.2%). In the mandible, the body of the mandible was most commonly involved (89.5%), with ragged margins (80%) and irregular pattern of involvement (75%) being the most common. Pathologic fracture was evident in 6 (30%) cases and floating tooth appearance was present in 10 (50%) cases. Only 3 (15%) cases demonstrated root resorption. Conclusion: Panoramic radiographs are valuable aids in diagnosing the involvement of jaw bones in oral malignancy, and thereby help in devising the treatment plan.